Incidence of fatal food anaphylaxis in people with food allergy: a systematic review and meta‐analysis. Issue 12 (December 2013) - Umasunthar, T.; Leonardi‐Bee, J.; Hodes, M.; Turner, P. J.; Gore, C.; Habibi, P.; Warner, J. O.; Boyle, R. J.
Summary Background Food allergy is a common cause of anaphylaxis, but the incidence of fatal food anaphylaxis is not known. The aim of this study was to estimate the incidence of fatal food anaphylaxis for people with food allergy and relate this to other mortality risks in the general population. Methods We undertook a systematic review and meta‐analysis, using the generic inverse variance method. Two authors selected studies by consensus, independently extracted data and assessed the quality of included studies using the Newcastle‐Ottawa assessment scale. We searched Medline, Embase, PsychInfo, CINAHL, Web of Science, LILACS or AMED, between January 1946 and September 2012, and recent conference abstracts. We included registries, databases or cohort studies which described the number of fatal food anaphylaxis cases in a defined population and time period and applied an assumed population prevalence rate of food allergy. Results We included data from 13 studies describing 240 fatal food anaphylaxis episodes over an estimated 165 million food‐allergic person‐years. Study quality was mixed, and there was high heterogeneity between study results, possibly due to variation in food allergy prevalence and data collection methods. In food‐allergic people, fatal food anaphylaxis has an incidence rate of 1.81 per million person‐years (95%CI 0.94, 3.45; range 0.63, 6.68). In sensitivity analysis with different estimated food allergy prevalence, the incidence varied from 1.35 to 2.71 per million person‐years. At age 0–19, the incidence rate is 3.25 (1.73, 6.10; range 0.94, 15.75; sensitivity analysis 1.18–6.13). The incidence of fatal food anaphylaxis in food‐allergic people is lower than accidental death in the general European population. Conclusion Fatal food anaphylaxis for a food‐allergic person is rarer than accidental death in the general population.